Information and thermodynamics: experimental verification of Landauer's Erasure principle. (10th June 2015) - Bérut, Antoine; Petrosyan, Artyom; Ciliberto, Sergio
Abstract: We present an experiment in which a one-bit memory is constructed, using a system of a single colloidal particle trapped in a modulated double-well potential. We measure the amount of heat dissipated to erase a bit and we establish that in the limit of long erasure cycles the mean dissipated heat saturates at the Landauer bound, i.e. the minimal quantity of heat necessarily produced to delete a classical bit of information. This result demonstrates the intimate link between information theory and thermodynamics. To stress this connection we also show that a detailed Jarzynski equality is verified, retrieving the Landauer's bound independently of the work done on the system. The experimental details are presented and the experimental errors carefully discussed